2013
DOI: 10.1097/mcg.0b013e31826be847
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Is a Risk Factor for Colonic Diverticulosis

Abstract: Alcohol use is a significant risk factor for colonic diverticulosis and may offer a partial explanation for the existing East-West paradox in disease prevalence and phenotype. Further studies are needed to investigate this association and its putative pathophysiological mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 36 publications
4
35
5
Order By: Relevance
“…It was found that Asians and blacks, including those from the Caribbean, were protected against left-sided diverticular disease compared to whites, with the odds ratio of left- The prevalence of diverticulosis has been estimated prospectively in several colonoscopy-based studies in Asia. The prevalence of diverticulosis in Lebanon was similar to that in the United States [12]; that is, the rate was 33% (mean age: 61 years), and most subjects had distal diverticulosis. However, other studies from the Middle East suggest a much lower prevalence.…”
Section: Diverticulosismentioning
confidence: 71%
See 1 more Smart Citation
“…It was found that Asians and blacks, including those from the Caribbean, were protected against left-sided diverticular disease compared to whites, with the odds ratio of left- The prevalence of diverticulosis has been estimated prospectively in several colonoscopy-based studies in Asia. The prevalence of diverticulosis in Lebanon was similar to that in the United States [12]; that is, the rate was 33% (mean age: 61 years), and most subjects had distal diverticulosis. However, other studies from the Middle East suggest a much lower prevalence.…”
Section: Diverticulosismentioning
confidence: 71%
“…The changing frequency of the bilateral type, with respect to both year and age, was similar to that of the left-sided type. In Asian countries, right-sided diverticulosis is thought to be of congenital origin, and diverticula developing subsequently on the left may extend into the bilateral colon [12,17].…”
Section: Diverticulosismentioning
confidence: 99%
“…However, as mentioned earlier, the prevalence is much lower in Africa and parts of Asia. The explanation for this East-West paradox in disease prevalence and phenotype is unclear but it has been suggested to be due to diet, particularly a high-fat diet, and alcohol consumption may also play a role in disease pathogenesis [8][9][10].…”
Section: Epidemiologymentioning
confidence: 99%
“…In the West, it is estimated that around 15-30% of the individuals will have diverticulosis by the age of 50 years [3] and as many as 60-70% by the age of 80 years [3,4], primarily located in the left colon. The prevalence is much lower in less industrialized parts of the world, such as Africa and parts of Asia, where it is found in only 4-5% of the population, with a pre-DOI: 10.1159/000490054 dominance of right-sided disease in Asian populations [5,6]. Recent evidence indicates that this prevalence is expected to further increase worldwide, possibly due to urbanization and the adoption of western lifestyles [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation